Representation of Forms of Sexual Harassment in Women Through Film in the Perspective of Muted Group Theory - Dwi Kartikawati; Chika Azrilla Aryanto (International Journal of Science and Society, 2023)
Sexual harassment is a serious issue that takes many forms, such as exploitation, coercion, or sexual abuse without consent. This type of harassment is a form of gender injustice that can manifest in various forms of marginalization and subordination towards women. Women can feel restricted in their ability to express themselves freely due to the dominance of men in society. As a result, there has been an increase in the number of cases of sexual harassment of women in society. This has prompted film directors to address the issue in their works, such as the film Virgin the Series. This research aims to analyze the representation of sexual harassment towards women in this film, which is available on the Disney+Hotstar application, using the perspective of muted group theory. The theoretical framework used in this study includes the concept of representation by Stuart Hall, the concept of sexual abuse, adolescence, and women, as well as Roland Barthes's semiotic theory and the grand theory of silence (The Muted Group Theory). The researchers utilized a qualitative research method and applied Roland Barthes's semiotics approach to analyze the text and visuals in this film. The findings indicate that the film portrays various forms of sexual harassment toward women, such as physical, oral, non-verbal, gestural, visual, and psychological harassment. These depictions further strengthen the position of women as subordinates, as explained by the muted group theory